An ultrafast electrochemical synthesis of Au@Ag core-shell nanoflowers as a SERS substrate for thiram detection in milk and juice. (15th February 2023) - Wang, Jingjing; Luo, Zisheng; Lin, Xingyu
Highlights: An innovative Au@Ag nanoflowers SERS substrate with high reproducibility and signal enhancement features. Fast and simple electrochemical reduction route for fabricating hybrid bimetallic Au@Ag-CSNFs. The extension of the designed substrate for screening of thiram residues. Applicability of the sensor in real milk and juice matrices with high recoveries. Abstract: An innovative bimetallic gold-silver core–shell nanoflowers (Au@Ag-CSNFs) SERS substrate has been synthesized by a facile electrochemical reduction process on an indium tin oxide (ITO) glass with a total fabrication time of 3 min. The proposed Au@Ag-CSNFs SERS substrate has been distributed evenly with numerous interstices and cavities between each branch, suggesting potential target trap sites and "hot spots". The Au@Ag-CSNFs administered good reproducibility of SERS signals collected from 140 random spots with a relative standard deviation and an enhancement factor of 13.62 % and 0.9 × 10 7, respectively. The substrate was further extended for the label-free SERS sensing of thiram residues with an ultra-low detection limit of 7.088 × 10 -8 mol/L. The designed probe was further subjected to thiram determination in real milk and juice samples with satisfactory recoveries (91.76–109.40 %). The rapidly synthesized Au@Ag-CSNFs substrate can be extended for SERS sensing in a variety of hazards in food settings.